Results of the Italian Pediatric Orthopedics Society juvenile flexible flatfoot survey: diagnosis and treatment options. Issue 1 (7th June 2021) - Pavone, Vito; Vescio, Andrea; Andreacchio, Antonio; Memeo, Antonio; Gigante, Cosimo; Lucenti, Ludovico; Farsetti, Pasquale; Canavese, Federico; Moretti, Biagio; Testa, Gianluca; De Pellegrin, Maurizio
Abstract : Supplemental Digital Content is available in the text. Abstract : The objectives of this study were to collect and analyze current diagnosis and treatment options of symptomatic flexible flatfoot (FFF), as well as to identify treatment expectations, among the members of the Italian Pediatric Orthopedics Society (SITOP). Diagnosis and treatment preferences were recorded according to a web-based survey. The survey was divided into six main sections: (1) general clinical parameters; (2) foot aspects; (3) X-ray angles (or lines); (4) expectations; (5) standard clinical assessment; (6) treatment options. One hundred and ten out of 248 SITOP members answered to the questionnaire. Age (85.5%), pain at the level of the plantar arch or fascia (61.8%), fatigue (59.1%) were the clinical parameters of crucial importance. Heel valgus (85.4%), flexibility (61.8%) and forefoot supination (47.3%) were identified as the most important foot aspects. Ninety-two responders (83.6%) identified the 'improved ability to walk longer without symptoms or discomfort' as the principal treatment expectation. Pain evaluated through the visual analog scale (VAS) was considered crucial in 31.8% of cases. All respondents confirmed they also treat patients with FFF surgically; in particular, 97.3% of SITOP affiliates declare to perform arthroereisis followed by lateral column lengthening (29.1%) and medializing calcaneal osteotomy (9.1%). Although in this survey heterogeneous findings for diagnosis and treatment of patients with symptomatic FFF within SITOP members were found, a large preference for age, heel valgus, flexibility as clinical aspects and parameters, as well as nonoperative treatment and arthroereisis, was reported.